Science for the poor: how one woman challenged researchers, ranchers, and loggers in Amazonia - Shanley, P. (2006)
In the lower Tocantins region of Brazil, one Amazonian woman questioned why scientists publish principally for elite audiences. Her experience suggests that the impact may be enhanced by also sharing data with people who depend upon forest goods. Having defended her family homestead near the city of Cameta against loggers in the late 1980s, Glória Gaia became interested in strengthening the information base of other villagers so that they would not lose their forests for meager sums. She challenged scientists to defy norms such as extracting data without giving back to rural villagers and publishing primarily for the privileged. Working with researchers, she helped them to publish an illustrated manual of the ecology, economics, management, and cultural importance of key Amazonian forest species. With and without funds or a formal project, she traveled by foot and boat to remote villages to disseminate the book. Using data, stories, and song, she brought cautionary messages to villages about the impacts of logging on livelihoods. She also brought locally useful processing techniques regarding medicinal plants, fruit, and tree oils. Her holistic teachings challenged traditional forestry to include the management of fruits, fibers, and medicines. A new version of the book, requested by the government of Brazil, contains the contributions of 90 leading Brazilian and international scientists and local people. Glória Gaia’s story raises the questions: Who is science for and how can science reach disenfranchised populations? Lessons for scientists and practitioners from Glória’s story include: broadening the range of products from research to reach local people, complementing local ecological knowledge with scientific data, sharing precautionary data demonstrating trends, and involving women and marginalized people in the research and outreach process.